PENGARUH TIKTOK LIVE STREAMING DAN KUALITAS PRODUK TERHADAP MINAT BELI ONLINE MASYARAKAT DI KABUPATEN JEMBER - Rizki, Iin Fatehatul; Siswanto, Adil (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2025)
In the current digital era, technological developments have transformed the way people conduct buying and selling transactions. One of the platforms widely used for business activities is the TikTok application, especially through its TikTok Live feature, which allows direct interaction between sellers and buyers. This study aims to determine the influence of TikTok Live and product quality on the online buying interest of the community in Semboro Subdistrict, Jember Regency. The research method used a quantitative approach with associative analysis, involving 96 respondents selected through an online questionnaire. The T-test results showed that TikTok Live (t-value = 4.220) and product quality (t-value = 6.902) have a positive and significant partial effect on online buying interest. Meanwhile, the F-test result (F-value = 117.614) indicated that both variables simultaneously have a positive and significant effect. Thus, TikTok Live and product quality are important factors in increasing online purchasing interest among the community.